Cash Flow Impact in the Micro Finance and Small Scale Industrial Development: Examining the Influence of Cash Flow on Microfinance and Small Scale Industrial Growth (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Microfinance is a form of financial services for entrepreneurs and small businesses lacking access to banking and related services. Cash flow, as the term is now most commonly used in financial analysis. In the present study we study the impact of cash flow in the micro finance and small scale industrial development.